Techno-economic analysis of a biomass-powered inclined bed dryer for maize drying - Adjei, Paxwell D; Akowuah, Joseph O; Obeng Akrofi, George; Awafo, Edward A (International Journal of Agricultural Research, Innovation and Technology, 2023)
The study assessed the technical performance and economic viability of a 200 kg capacity biomass-powered inclined bed dryer for drying maize. The dryer recorded an average air temperature of 73.54˚C in the plenum, which reduced the moisture content from 23.25% (w.b) to 13.61% (w.b) at a drying time of 2 hours 40 minutes. This resulted in a drying rate, drying efficiency, and specific energy consumption of 9.50 kg/h, 71.37%, and 25.70 MJ/kg, respectively. The germination potential of dried maize grains was 80% compared to 93% for grains assessed before drying. Stress-crack analysis revealed a lower percentage of no-cracks for dried maize (71%) than maize gains before drying (98%). There was a statistically significant difference between the dried and the undried maize grains for germination viability (p = 0.01) and stress crack analysis (p = 0.00) at α=0.05. At a drying charge of US$ 2.4 per 100 kg bag of maize, the investment cost could be regained at a pay-back period of 6 months and 15 operation days and a benefit-cost ratio of 1.27. The drying system is economically viable at net present value of US$ 1313.48 and internal rate of return of 44%. Evidently, adopting the dryer could contribute to reducing post-harvest loss of maize at the smallholder level and increase farmer's income. Int. J. Agril. Res. Innov. Tech. 13(1): 15-24, June 2023